Observations of Seasonal Movement from a Single Tag Release Group of Pacific Cod in the Eastern Bering Sea. Issue 1 (10th December 2014) - Rand, Kimberly M.; Munro, Peter; Neidetcher, Sandra K.; Nichol, Daniel G.
Abstract: The Pacific Cod Gadus macrocephalus in the eastern Bering Sea is the target of one of the most lucrative fisheries in Alaska; however, relatively little is known about the movement of Pacific Cod and how this interacts with intense fishing on local spawning aggregations of cod every spring (January–April). This study aimed to draw inferences on Pacific Cod movement using a single tag release group of fish and the fishery as a representative for movement by qualitatively examining both temporal and spatial patterns of tag recoveries. Based on the tag recoveries in this study and past genetic studies, there is evidence that Pacific Cod show both homing tendencies and site fidelity during the spring when large aggregations of cod form to spawn. This study also supports results from an earlier study on Pacific Cod movement in this region and presents new insights into cod movement patterns. The cod in this tag release group were widely distributed across the Bering Sea during the summer and fall months and returned to the vicinity of the release site in the spring, presumably to spawn. Understanding the movement of cod and their interactions with the fishery is essential to the successful management of the Pacific Cod stock. Received May 12, 2014; accepted October 7, 2014